Desemprego: causas, conseqüências e possíveis soluções - Reinert, José Nilson (2001)
This paper presents some questions which the author considers relevant about unemployment. lt presents the concept of unemployment, some causes, consequences and possible solutions to the question. It also presents some difficulties regarding the elaboration and implementation of policies to minimize the problem of unemployment, the political questions, the methodological questions to account the unemployment, the new liberal ideology prevailing today and the incompetente and the indifference of the public and of the private sector about unemployment. KEYWORDS: Unemployment; Employment; Work